Evektivitas Briket Bioarang Dari Limbah Kulit Pisang Raja (Musa acuminata) dan Limbah Kulit Nangka (Artocarpus heterophyllus) - Kholifah, Cici; Aprilia, Naura Nur; Ni'am, Achmad Chusnun (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Utilization of banana peel waste and jackfruit peel waste as biobriquettes so that it can reduce environmental pollution and be used as a renewable resource. The purpose of the research is to tackle environmental pollution by making biobriquettes as a renewable alternative energy. In this study, two variations of adhesives were used, namely tapioca starch and wheat flour adhesives with a concentration of 5% and 10% respectively. The test parameters studied included moisture content, ash content, volatile matter, fixed carbon, calorific value, and combustion rate. The results showed that the quality of the biobriquettes produced from the four parameters were moisture content 0.35%-0.71%, ash content 0.48%-0.99%, volatile matter 2.31%-3.40%, fixed carbon 95.48%-96.80%, calorific value 3524.85kcal/g-5198.66kcal/g, drop test 0.01%-0.06%, flame time 133.50 minutes 162.50 minutes, and burning rate 28.62 g/sec-36.54 g/sec. The heating value test parameter is the main parameter to determine the quality of briquettes. Biobriquettes with a composition of 25% plantain peel waste + 65% jackfruit peel waste + 10% tapioca flour adhesive have the best quality with an average of 5439.67 cal/g.